Recurrent Spontaneous Bilateral Subdural Hemorrhage as a Consequence of High-Cervical Spontaneous CSF Leak—Lessons for Neurosurgeons - Venugopal Subramaniam; Sibhi Ganapathy; S. Shivananda; K. N. Nagabhushan; Raghu Murthy (Indian Journal of Neurosurgery)
Spontaneous intracranial hypotension (SIH) is rare. It presents as intractable posture headache and is identified by radiological findings. It is confirmed by cerebrospinal fluid (CSF) manometry and myelography, and treatment is carried out with the help of epidural blood patch (EBP) therapy. SIH presenting with spontaneous bilateral recurrent subdural bleeds is uncommon. The cause being a high-spinal CSF leak is even more uncommon! Our patient had recurrent bilateral spontaneous chronic subdural hematomas. Myelographic examination of the spine showed a C1–C2 level leak of CSF. He was taken up for open microsurgery, and the leak was identified and closed with fibrin glue. The patient however deteriorated the next day. An EBP was applied in the lumbar region to cover the myelogram lumbar puncture site. We present a review of literature and an algorithm to detect the elusive CSF leak and effect definitive treatment, either open or EBP, to treat the source of the problem.